Implementation of teleHealth using SKEDit for protein diet education for diabetes patients - Khoirul Rista Abidin; Eka Riana (Media Keperawatan Indonesia, 2021)
A protein diet is an alternative to control hyperglycemia and hyperlipidemia conditions in diabetic patients. However, for the program to run optimally, the implementation of technology in the form of TeleHealth is needed to help educate patients on a regular and flexible basis. The purpose of this study was to analyze the effectiveness of implementing TeleHealth using the SKEDIt application for protein diet education in diabetic patients. Methods: This research is a quasi-experimental study, pre and post-test with a control group. The subjects involved were 20 diabetic patients, divided into 2 groups (intervention and control). Parameters analyzed were lipid profile and blood glucose levels. There was no difference in lipid profile and blood glucose levels between the intervention and control groups (p > 0.05). However, there was a difference between the pre and post-test on cholesterol parameters in the lipid profile examination of the control group: p=0.031 and LDL p=0.021 (p <0.05). Implementation of TeleHealth using SKEDit may be an effective recommendation to support health education methods but needs to be supported by good patient compliance.